Reimbursement and use of oral anticoagulants during 2014-2022 - A register-based study - Aarnio Emma; Huupponen Risto; Martikainen Janne; Korhonen Maarit J (Netherlands, 2025)
Background: Vitamin K antagonists, warfarin in particular, have been the mainstay of anticoagulation therapy, but their use has declined in many countries since direct oral anticoagulants (DOACs) have entered the market.
Objective: To examine utilization trends of oral anticoagulants (OACs) in Finland considering the reimbursement of DOACs and changes to national treatment guidelines for the treatment of atrial fibrillation (AF).
Methods: Both public, aggregated data on reimbursed OAC dispensations and individual-level data on electronic dispensations during 2014-2022 were applied. Data on electronic dispensations during 2015-2016 were used to study OAC initiations. Data on entitlements to reimbursement for DOACs came from public data.
Results: In 2014, there were almost 20,000 DOAC users, rising to 214,000 in 2022. The number of warfarin users declined since 2015 from over 181,000 to around 59,000 users in 2022, DOACs exceeding warfarin in the number of users in 2019. The total DOAC costs were higher than warfarin costs each year. Rivaroxaban was the most widely used DOAC during 2014-2018, and apixaban during 2019-2022. In 2015, there were more warfarin (56.7%) than DOAC (43.3%) initiators, but the result was opposite for 2016 (warfarin 39.4%, DOACs 60.6%). The number of individuals entitled to reimbursement for DOACs has increased steadily, and in 2022, there were over 196,000 individuals entitled to this reimbursement due to AF.
Conclusions: The uptake of DOACs in Finland appears to have been gradual and slower than in many other countries. During the 2010s, the treatment guidelines for AF were more cautious in recommending DOACs than the European guidelines. The use of DOACs increased as their reimbursement became less restrictive.